Роль філософії в житті сучасного суспільства: питання без відповідей - Петрушенко, Віктор (Lviv Politechnic Publіshing House, 2016)
Розглянуто п’ять сфер суспільного життя, в яких наявна філософія: інтелектуальна культура та ерудиція людини, внутрішній світ людини, освіта, наука та державні програми і рішення. Констатовано, що в означених сферах філософія втратила свій авторитет. Застосовано метод порівняльного аналізу. Перспективи дослідження: як філософія має допомогти сучасній людині самовизначитися. The article deals with acute issues related to the state of modern philosophy and its place in modern society on background of the common thesis about the death of philosophy or exhaustion of its creative resources. The author elaborates on the theme by analyzing five major spheres of public life in which presence of philosophy is obvious and traditional: it is intellectual culture and erudition of the person, interior individual world of a man, education, science and governmental programs and solutions. The article states that in all these spheres philosophy has lost its weight and authority, in most cases in these spheres it is not considered as important and necessary. Particularly, in the field of education the volume of the study of philosophy has been substantially narrowed, in the field of science complex and controversial questions deterred scientists from philosophy, and government administration and creators of social programs often regard to philosophy with blatant irony. In the field of scientific knowledge and engineering solutions, thesis that science is itself a philosophy remains acceptable. The author believes that philosophy should return to its main vocation, and will help a modern person to define themselves in extremely difficult conditions of modern life. The article is based on methods of comparative analysis, unity of the historical and the logical. Positive prospects for philosophy, according to the author, are connected with its refusal of the role of maintenance in different spheres of activity and with awakening in a person of impulses to self-cognition and self-improvement.
The role of philosophy in life of contemporary society: questions without answers
Keywords: смерть філософії; узагальнення і розуміння; самопізнання і самовизначення; death of philosophy; generalizations and understanding; self-knowledge and self-determination